DELINQUENCY OF «PHARMACY DRUG ADDICTION» AS A DETERMINING FACTOR IN STRENGTHENING CONTROL OVER THE CIRCULATION OF MEDICINES - V. Zhukovsky; N. Dovgolyuk (Гуманитарные и юридические исследования)
The problems of illicit trafficking in narcotic drugs and psychotropic substances and their non-medical consumption on the scale of the spread and development of drug addiction, as well as the difficulties of anti-drug exposure were a global problem of the world community in the XX century and remain relevant in the XXI century. «Pharmacy» drug addiction has become a real disaster for the country, rapidly spreading to all regions and subjects of the Russian Federation. Pharmaceutical organizations as subjects of the pharmaceutical market are obliged to ensure the availability of medicines, including those containing narcotic drugs, psychotropic substances and their precursors for use for medical purposes and at the same time are obliged to provide conditions to prevent the possibility of illicit traficking in these drugs. The so-called «pharmaceutical drugs» are in special demand among drug addicts. These are pregabalin-contain-ing drugs that are not poisonous or potent tools and in its composition does not contain any narcotic or psychotropic substances. Their use when not prescribed by a doctor (including unintentional way, in large doses, in combination with other substances or alcohol) causes drug intoxication, as well as persistent addiction. Persons who use these drugs without doctor's prescription, as a rule, are violators of public order, are prone to committing crimes of ordinary orientation, thereby affect (in the direction of deterioration) on the operational situation, damage the reputation of public authorities. The article analyzes the state of issues and problems in the sphere of circulation of medicines and their non-medical consumption, identifies problematic aspects of law enforcement, and identiies the main directions of improving prevention and organizational work in this direction.